PENGGUNAAN METODE MIND MAPPING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA TUNARUNGU KELAS 5 DI SLB - Resista Putri, Ayu (Jurnal Pendidikan Khusus, 2016)
ABSTRACT   The difficulty in receiving auditive information caused hearing impairment children got vocabulary limitedness. It caused the low of speaking skill to hearing impairment children. In the school age, one of the aspects which should be belonged to hearing impairment children was reading comprehension ability which would support the cognitive ability of hearing impairment children. This research purpose was to prove whether there was influence of using mind mapping method toward reading comprehension skill to class 5 of hearing impairment students in SDLB-B Karya Mulia I Surabaya. The research kind used was pre-experiment with “the one group pre-test post-test design”. The subject was class 5 of hearing impairment students in SDLB-B Karya Mulia I Surabaya numbering 7 students who had difficulty in reading comprehension. The data collection technique was collected using test and observation. The data analysis technique used statistic non parametric wilcoxon match pair test. Appropriate with the result of data analysis, it indicated that using mind mapping method influenced significantly toward reading comprehension ability to class 5 of hearing impairment students in SDLB-B Karya Mulia I Surabaya. It was shown by good comprehension in answering exercises about the reading content.   Keywords: reading comprehension, mind mapping.